IFC Annual Report 2005 : Investing in Progress with Experience, Innovation, and Partnership, Volume 2. Financial Statements, Projects, Portfolio, and Organizational Information - International Finance Corporation (Washington, DC, 2012)
The International Finance Corporation is at the forefront of private sector development: it is redefining how poverty can be reduced and lives improved through a stronger private sector in emerging markets. Accomplishing this goal means reaching people, regions, and sectors that have not yet shared in the overall growth of emerging markets. It means innovation-forging new partnerships with governments and other multilateral institutions, identifying new roles for the private sector, creating products that develop financial markets, and making it easier for disadvantaged people to launch a business or own a home. It means building on significant strengths in many countries and industries-helping established enterprises become more competitive and sustainable as they expand their operations or extend their reach into new markets. It also means bringing to developing economies proven products and techniques, both from industrialized countries and, increasingly, from other developing countries. Above all, it means tailoring global expertise to local needs. This annual report outlines the strategic objectives of the institution in expanding access to finance, increasing private participation in key sectors, helping successful enterprises grow, focusing where needs are greatest, and ensuring sustainability.